Purification and characterisation of glutathione reductase from scorpionfish (scorpaena porcus) and investigation of heavy metal ions inhibition - Kübra Işık; Ercan Soydan (Taylor & Francis Group, 2023)
In the current study, glutathione reductase was purified from Scorpion fish (Scorpaena porcus) liver tissue and the effects of heavy metal ions on the enzyme activity were determined. The purification process consisted of three stages; preparation of the homogenate, ammonium sulphate precipitation and affinity chromatography purification. At the end of these steps, the enzyme was purified 25.9-fold with a specific activity of 10.479 EU/mg and a yield of 28.3%. The optimum pH was found to be 6.5, optimum substrate concentration was 2 mM NADPH and optimum buffer was 300 mM KH2PO4. After purification, inhibition effects of Mn+2, Cd+2, Ni+2, and Cr3+, as heavy metal ions were investigated. IC50 values of the heavy metals were calculated as 2.4 µM, 30 µM, 135 µM and 206 µM, respectively.